Pemberdayaan Masyarakat Melalui Budidaya Tambak Ikan Di Sungai Kahayan Kota Palangka Raya - Wahidin Wahidin; Hengki Tornado (Jurnal Ilmiah Kanderang Tingang, 2022)
This study aims to describe and understand how community participation in the management of fish ponds in the Pahandut Sebrang sub-district, Palangka Raya City and what are the supporting and inhibiting factors. This research is a descriptive research with a qualitative approach. The research subjects were local fish pond community members. Methods of collecting data by observation, interviews and documentation, with data analysis techniques, used data reduction, display data and draw conclusions. Triangulation is done to explain the validity of the data. The results of the study show (1) Community participation in the management of fish ponds is quite high and is their main job. (2) The supporting factor for this business is the condition of the Kahayan river which is quite fast, which is very suitable for fish ponds. Besides that, the harvest is not difficult to sell because it is very close to the city center of Palangka Raya. While the inhibiting factor is the lack of public capital, so there is a need for a capital loan or investors to work together in the business.